Analysis of Flow Changes to the Foot after Sacrifice of One of the Major Arteries - DURMUŞ KOCAASLAN, FATMA NİHAL; BAYRAMİÇLİ, MEHMET NURİ ÜMİT (THIEME MEDICAL PUBL INC, 2009)
The objective of this Study was to find out whether a compensatory increase in blood flow to the foot is observed after sacrifice of one of the tibial arteries. Eleven patients who had one of the tibial arteries as the recipient artery of free tissue transfer to their lower extremities were included. The arterial diameter, cross-sectional area, maximum flow velocity, minimum flow velocity, and flow rate were measured by a Doppler ultrasound in the nonrecipient tibial artery and perforating peroneal artery in the operated limb. The same parameters were measured in the anterior and posterior tibial arteries and the perforating peroneal artery in the contralateral limb. The arterial diameter, cross-sectional area, flow velocity, and flow rate were increased significantly in the nonrecipient tibial artery of the operated limb with respect to the same artery on the contralateral limb. The same changes were not demonstrated in the perforating branch of the peroneal artery. Total blood flow to the foot in the operated extremity was not different from that of the nonoperated foot. The results reveal that if a major feeder to the foot is sacrificed, the other tibial artery compensates for it, and resting blood supply to the foot is not altered.
Keywords: Lower extremity reconstruction; blood flow to the foot; Doppler flow meter analysis; RADIAL FOREARM FLAP; DONOR-SITE; BLOOD-FLOW; MORBIDITY